Potential drug interactions and profile of antimicrobials prescribed for outpatient use in the interior of Bahia - Santos, Beatriz da Silva (2021)
This study aimed to analyze the profile of antimicrobials and potential drug interactions, involving these drugs, prescribed for outpatient use in the interior of Bahia. This is a cross-sectional study, carried out based on the analysis of 404 antimicrobial prescriptions listed in the DRC no. 20/2011, made available by the store of a chain of pharmacies, referring to the period of May 2018. The analysis of drug interactions (IM) was made using the MICROMEDEX® version 2.0 database (2011). The most prescribed class of antimicrobials was that of β-lactams (27.7%), followed by macrolides (25.3%) and fluoroquinolones (18.3%). As for the drugs prescribed in combination, there was a predominance of non-steroidal anti-inflammatory drugs (23.3%) and analgesics (19.8%). A total of 20 different drug interactions were observed, involving antimicrobials, most frequently for ciprofloxacin. After analyzing the interactions, it was possible to verify the risks related to drug associations that can be minimized with the analysis of the prescription by a pharmaceutical professional and alert systems in electronic prescription.